Prevalence of colistin resistance of Klebsiella pneumoniae isolates in Iran: a systematic review and meta-analysis - Negar Narimisa; Forough Goodarzi; Shirin Bavari (BMC, 2022)
Abstract Objective Klebsiella pneumoniae is a gram-negative pathogen common cause of nosocomial infections. Colistin is a last resort antibiotic to treat infections caused by K. pneumoniae. In recent years, the resistance rate to colistin has increased in K. pneumoniae. This study evaluated the prevalence of colistin resistance of K. pneumoniae isolates in Iran using a systematic review and meta-analysis. Method A systematic search was performed for relevant articles until August 2021 in the following database: PubMed, Scopus, SID and Google Scholar. The pooled prevalence of colistin resistance in clinical K. pneumoniae isolates analyzed using Comprehensive Meta-Analysis Software (CMA). Results Finally, 19 articles with appropriate criteria were included in the meta-analysis. Our results showed 6.9% of the pooled prevalence of colistin resistance in clinical K. pneumoniae isolates in Iran. The results of subgroup analysis demonstrated increase resistance of colistin from 4.8%; (95% CI 1.5-13.9%) in 2013-2018 to 8.2%; (95% CI 3.4-18.6%), in 2019-2021. Also, the results of our study showed a strong association between the carbapenem producing K. pneumoniae and increased resistance to colistin. Conclusions This study showed a high prevalence of colistin resistance in K. pneumoniae isolates. It is recommended that regular evaluation be performed to control colistin resistance.